Sustainable development of the border city in the context of European integration processes and decentralization in Ukraine (on the example of Lutsk, 2008-2020) - Salnikova, Svitlana; Khanin, Oleksandr (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
Regional development of the territories of Ukraine neighboring the countries of the European Union is the focus of research by different institutions of the EU. The authors analyzed the sustainable development of the border city in the social and economic spheres, taking into account local, national and European integration contexts. Sociological research data, statistics and some open data were used to analyze socio-economic indicators in the dynamics. However, their analysis is complicated by decentralization – a new territorial structure of Ukrainian regions approved in 2020, and it is impossible to predict the development of the city within the new boundaries due to the lack of statistics collected in accordance with the new administrative division of territories. Sociological research has shown a social climate in the city in which the residents associate the lack of social benefits [1] with problems at the state level, not local, need new knowledge, skills, experience etc., and for this purpose they are focused on migration. The dynamics of population aging in the city and the region is not critical, but local authorities are forced to address the issue of returning people aged 65+ to the labor market, or support economy sectors in which they can realize their experience and potential. Professional failure of people aged 41+ requires quality education and an innovative economy. The Volyn Region and the city of Lutsk are characterized by consistently high quality of school education; it is a good basis for economic development. The paradox of the city's economic development is that with a good pace of enterprise development and revenues to budget, population incomes are low. Issues of human resource quality and quality of life are the priority issues of decentralized territories of Volyn.